Diagnostic overshadowing and other challenges involved in the diagnostic process of patients with mental illness who present in emergency departments with physical symptoms--a qualitative study. - Guy Shefer; Claire Henderson; Louise M Howard; Joanna Murray; Graham Thornicroft (PLoS ONE)
We conducted a qualitative study in the Emergency Departments (EDs) of four hospitals in order to investigate the perceived scope and causes of 'diagnostic overshadowing'--the misattribution of physical symptoms to mental illness--and other challenges involved in the diagnostic process of people with mental illness who present in EDs with physical symptoms. Eighteen doctors and twenty-one nurses working in EDs and psychiatric liaisons teams in four general hospitals in the UK were interviewed. Interviewees were asked about cases in which mental illness interfered with diagnosis of physical problems and about other aspects of the diagnostic process. Interviews were transcribed and analysed thematically. Interviewees reported various scenarios in which mental illness or factors related to it led to misdiagnosis or delayed treatment with various degrees of seriousness. Direct factors which may lead to misattribution in this regard are complex presentations or aspects related to poor communication or challenging behaviour of the patient. Background factors are the crowded nature of the ED environment, time pressures and targets and stigmatising attitudes held by a minority of staff. The existence of psychiatric liaison team covering the ED twenty-four hours a day, seven days a week, can help reduce the risk of misdiagnosis of people with mental illness who present with physical symptoms. However, procedures used by emergency and psychiatric liaison staff require fuller operationalization to reduce disagreement over where responsibilities lie.